Biodiversity and origin of the microbial populations isolated from Masske, a traditional Iranian dairy product made from fermented Ewe's milk. (16th May 2016) - Ghiamati, Fariba; Yavarmanesh, Masoud; khomeiri, Morteza; Maghsoudlou, Yahya
Abstract : Masske is a traditional Iranian dairy product containing 50% butterfat made from fermented ewe's milk. Overall, 672 bacterial isolates were collected from ewe's milk, fermented milk (FM) and Masske samples that were produced in households located in southern regions of the Khorasan Province in Iran. To identify lactic acid bacteria in these samples, a total of 79 Gram‐positive and catalase‐negative isolates were analysed. The identification of isolates was achieved by phenotypic and sequential analysis of the 16S rRNA gene. Enterococcus faecium and Aerococcus viridans were the most frequently isolated species in the samples, but the most commonly present bacteria in Masske were Streptococcus thermophilus.